The influence of soft wheat grain germination on its technological properties - Darigash Shaimerdenova; Aigul Omaraliyeva; Baltash Tarabayev; Zhanar Chakanova; Damira Iskakova; Gaini Sarbassova; Maigul Kizatova; Sandugash Anuarbekova (PLoS ONE, 2025)
This study evaluates the impact of controlled germination on the technological properties of soft wheat grain (Tәuelsizdik variety) to determine its suitability for flour production. Grain was germinated for 24, 48, and 72 hours and incorporated into commercial flour at varying ratios (5%, 10%, and 15%) with gluten contents of 26%, 28%, and 30%. Technological properties including flour strength (W), water absorption capacity (WAC), and falling number (FN) were assessed using standard analytical methods and optimized through a Box–Behnken design with response surface modeling. Results revealed that increasing germination time significantly reduced gluten content, FN, and dough rheological parameters such as tenacity and elasticity, while increasing extensibility. Optimal technological performance was achieved with 29.8% gluten content, 24 hours of germination, and 8.2% germinated grain, yielding strong flour characteristics: W = 307.6 × 10 ⁻ ⁴ J, WAC = 54.9%, and FN = 180.4 s. The study highlights that, under optimal conditions, germinated soft wheat grain can be effectively utilized in flour production without compromising quality, offering a valuable strategy for processing sprouted grain resulting from unfavorable harvest conditions.